PENGARUH SEMANGAT KERJA PEGAWAI TERHADAP EFEKTIVITAS PELAYANAN - Lingga Pratama E42008022 (FISIP Universitas Tanjungpura Pontianak, 2012)
Writing this thesis aims to determine how much influence the morale factor of the effectiveness of servicesin health centers Pawan Kedondong Ketapang Delta District. The title is taken based on issues relating to theimplementation of health services at the health center district Kedondong Delta Pawan Ketapang so the authorsassume that employee morale is a factor affecting the problem.This study used quantitative research methods to the type of explanative. This study begins with the initialobservation and research proposal, and then build and test the validity and reliability of the questionnaire. After that,the questionnaire distributed to respondents and analyzed in the research report (thesis). Research Areas in DeltaDistrict Health Center Kedondong Pawan Ketapang. Subjects were Civil Servants (PNS) and honorary Delta HealthCenter Kedondong Kecmatan Pawan Ketapang.The conclusion of this study is employee morale effect on the effectiveness of services in health centersPawan Kedondong Ketapang Delta District. Therefore, the authors provide recommendations to improve employeemorale so that the effectiveness of the service centers in district health centers Delta Kedondong Pawan Ketapanggetting better.Keywords: Morale, Services, Services Effectiveness.